Comparative study of Hofstede's and Trompenaars' culture dimensions in Singapore - Gan, Kah Hua (2008)
An understanding of culture has become increasingly important today. This paper seeks to compare the cultural models of Hofstede & Trompenaars, as well as creating a Singapore cultural profile.